Organizing management of arabic language program in islamic senior high school of west seram maluku - Ulfa Mawaddah Ahmad Opier; Nuril Mufidah (12 Waiheru, 2022)
This study to describe the stages of the process and the principles of implementing the Organizing Management function in the Arabic Language Program in Islamic Senior High School of West Seram. This research uses a descriptive qualitative method. Data collection technique used are non-participant observation, in-depth interview, and documentation. Observation of the running of the Club. Interviews were conducted by interviewing the principal, Arabic teacher and club tutor. The analysis technique adopts the Miles and Huberman model, namely Data Reduction, Data Presentation and Drawing Conclusion. The research showed that: (1) The Arabic club of Islamic Senior High School of West Seram applies two organizing management functions, namely determining the plans and objectives of the Arabic Club, and conducting evaluations; (2) Three principles of Organizing management have been applied in the Arabic Club, including power and responsibility by club tutors, direction and teamwork. It is known that the organizing management at the Arabic Club of Islamic Senior High School of West Seram is not well structured because there is no organizational structure and a clear division of organizational tasks.